2007
DOI: 10.1892/0891-6640(2007)21[356:iadoh]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Airway Disease of Horses

Abstract: The purpose of this consensus statement is to provide a review of current knowledge and opinions concerning inflammatory airway disease (IAD) and to help practitioners differentiate IAD from heaves (or recurrent airway obstruction; RAO) and other inflammatory respiratory diseases of horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
187
4
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(202 citation statements)
references
References 49 publications
5
187
4
6
Order By: Relevance
“…Among noninfectious conditions, both SAA and haptoglobin are increased in horses with heaves compared to controls kept in the same environment 8. The lack of differences between IAD and non‐IAD horses studied here could be because of the lesser degree of inflammation in IAD compared to heaves,9 or because of a relatively high baseline level of inflammation in this population of poor performers. The higher levels and frequency of detection of SAA in this study compared to levels and frequency previously reported in heaves supports the latter hypothesis (90 and 81% of non‐IAD and IAD horses had detectable SAA in this population, while only in 17% of controls and 67% of heaves‐affected horses had detectable SAA levels8).…”
Section: Discussionmentioning
confidence: 65%
“…Among noninfectious conditions, both SAA and haptoglobin are increased in horses with heaves compared to controls kept in the same environment 8. The lack of differences between IAD and non‐IAD horses studied here could be because of the lesser degree of inflammation in IAD compared to heaves,9 or because of a relatively high baseline level of inflammation in this population of poor performers. The higher levels and frequency of detection of SAA in this study compared to levels and frequency previously reported in heaves supports the latter hypothesis (90 and 81% of non‐IAD and IAD horses had detectable SAA in this population, while only in 17% of controls and 67% of heaves‐affected horses had detectable SAA levels8).…”
Section: Discussionmentioning
confidence: 65%
“…Horses with heaves, including those with recurrent airway obstruction (RAO) and summer pasture‐associated RAO, exhibit marked lower airway inflammation and obstruction associated with frequent coughing, increased respiratory effort at rest and exercise intolerance 1, 2, 3. Clinical signs and airway obstruction can be reversed by administration of corticosteroids, bronchodilators, or changing the environment 4, 5, 6.…”
mentioning
confidence: 99%
“…Hypersensitivity disorders are important in horses, with recurrent airway obstruction (RAO), insect bite hypersensitivity (IBH), and urticaria (URT) among the most frequently observed 1, 2, 3, 4, 5, 6. In other species, including humans, dogs, and cats, a combined occurrence of multiple hypersensitivities (MHS) affecting different organ systems has been described.…”
mentioning
confidence: 99%